(untitled) (International Journal of Food and Nutritional Sciences, 2024)
Injection molding is a manufacturing process for producing part for both thermoplastic and thermosetting plastic material. Objective of this project to determine the parameter effect to the war page and shrinkage of the hand phone casing and to determine the optimization parameter for reduce the war page and shrinkage the most important problems in production of plastic parts using injection molding. The relationship between input and output of the process is studied using regression method and Analysis of Variance technique. The selected input parameters are melting temperature, injection pressure, packing pressure and packing time. Effect of these parameters on the shrinkage of above mentioned materials is studied using mathematical modeling. Similarly productivity will be decreased while the efforts are channelized to enhance quality. To ensure high quality and productivity, it is necessary to optimize machining parameters. Various responses of quality of injection moulding process has been studied on the basis of performance parameters and methods. This paper aims to present plastic injection moulding process conditions. The processing conditions satisfied quality based product manufacturing.